Identification of markers associated with estimated breeding value and horn colour in Hungarian Grey cattle - Attila Zsolnai; András Kovács; Endre Kaltenecker; István Anton (Animal Bioscience, 2021)
Objective This study was conducted to estimate effect of single nucleotide polymorphisms (SNP) on the estimated breeding value of Hungarian Grey (HG) bulls and to find markers associated with horn colour. Methods Genotypes 136 HG animals were determined on Geneseek high-density Bovine SNP 150K BeadChip. A multi-locus mixed-model was applied for statistical analyses. Results Six SNPs were identified to be associated (−log10P>10) with green and white horn. These loci are located on chromosome 1, 3, 9, 18, and 25. Seven loci (on chromosome 1, 3, 6, 9, 10, 28) showed considerable association (−log10P>10) with the estimated breeding value. Conclusion Analysis provides markers for further research of horn colour and supplies markers to achieve more effective selection work regarding estimated breeding value of HG.